2017
DOI: 10.1016/j.jpowsour.2017.02.042
|View full text |Cite
|
Sign up to set email alerts
|

Divalent-doped Na3Zr2Si2PO12 natrium superionic conductor: Improving the ionic conductivity via simultaneously optimizing the phase and chemistry of the primary and secondary phases

Abstract: NASICON is one of the most promising sodium solid electrolytes that can enable the assembly of cheaper and safer sodium all-solid-state batteries. In this study, we perform a combined experimental and computational investigation into the effects of aliovalent doping in NASICON on both bulk and grain boundary (secondary phase) ionic conductivity. Our results show that the dopants with low solid solubility limits in NASICON lead to the formation of a conducting (less insulating) secondary phase, thereby improvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
104
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(117 citation statements)
references
References 50 publications
12
104
1
Order By: Relevance
“…Our theory also reveals the underlying origin for the enhancement in bulk conductivity observed in previous doped NaSICON materials, [27][28][29][30] in which the Na +ion concentration increases as a compenstation of the aliovalent doping (Zn 2+ , Ca 2+ , Ba 2+ , Y 3+ , Sc 3+ ) at the Zr site. This finding supports the results of theory described above, which suggests that the Na + -ion concentration is a main factor determining the bulk conductivity in NaSICON materials.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…Our theory also reveals the underlying origin for the enhancement in bulk conductivity observed in previous doped NaSICON materials, [27][28][29][30] in which the Na +ion concentration increases as a compenstation of the aliovalent doping (Zn 2+ , Ca 2+ , Ba 2+ , Y 3+ , Sc 3+ ) at the Zr site. This finding supports the results of theory described above, which suggests that the Na + -ion concentration is a main factor determining the bulk conductivity in NaSICON materials.…”
supporting
confidence: 56%
“…[21][22][23] The total ion conductivity varies by an order of magnitude with x and the highest value (0.67 mS cm −1 at 300 K) was reported in the monoclinic phase where x ≈ 2.0, that is, Na 3 Zr 2 Si 2 PO 12 . [28][29][30] Guin and Tietz [31] reviewed various substituted NaSICONtype materials and concluded that the optimum ion conductivity is achieved at a Na + -ion content of ≈3.3 mol formula unit −1 . Researchers have primarily focused on using doping strategies to further improve the conductivity of this system, with Sc-substituted Na 3.4 Sc 0.2 Zr 1.8 (SiO 4 ) 2 (PO 4 ) exhibiting the highest reported conductivity at room temperature (6.2 mS cm −1 for the bulk value and 4.0 mS cm −1 for the total value, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Figure d displays the Arrhenius curves of NZTO, NZTO‐G0.1, and typical sodium oxide SSEs. At about 100 °C, NZTO‐G0.1 gives a higher ionic conductivity than single crystal β / β ′′‐alumina, Na 3 Zr 2 Si 2 PO 12 (NASICON), and Ti‐doped NASICON, but lower than Y‐doped NASICON . Table shows the E a of each oxide SSE displayed in Figure d. NZTO‐G0.1 gives a lower E a than NASICON, and its ionic conductivity is higher than other sodium oxide solid electrolytes, except for Y‐doped NASICON.…”
Section: Figurementioning
confidence: 99%
“…Other ions such as La 3+ , Sc 4+ , Mg 2+ and Ge 4+ also have been doped in NZSP solid electrolyte, and high ionic conductivities up to 10 −3 S cm −1 are achieved at room temperature . Moreover, a small amount of conductive phase, such as Na 3 PO 4 and Na 3 La(PO 4 ) 2 , can also facilitate the improvement of the ionic conductivity . Besides, excellent densification is also an important factor for the enhancement of ionic conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al. reported that Mg‐doped Na 3 PO 4 compound is a conducting second phase, and it can improve the grain boundary conductivity of NZSP by decreasing the grain boundary resistance for Na + transport . Consequently, high ionic conductivity of 2.21 mS cm −1 at 300 K, low electronic conductivity of 1.76×10 −5 mS cm −1 at 300 K, and low activation energy of ∼0.27 eV are achieved for the optimized Mg 2+ /F − co‐assisted NZSP solid electrolyte.…”
Section: Introductionmentioning
confidence: 99%